Magnetic Properties of Fe3o4 Antidot Arrays Synthesized by Afir: Atomic Layer Deposition, Focused Ion Beam and Thermal Reduction - Escrig-Murua, J; Pereira-Abarca, A (BEILSTEIN-INSTITUT, 2018)
Magnetic films of magnetite (Fe3O4) with controlled defects, so-called antidot arrays, were synthesized by a new technique called AFIR. AFIR consists of the deposition of a thin film by atomic layer deposition, the generation of square and hexagonal arrays of holes using focused ion beam milling, and the subsequent thermal reduction of the antidot arrays. Magnetic characterizations were carried out by magneto-optic Kerr effect measurements, showing the enhancement of the coercivity for the antidot arrays. AFIR opens a new route to manufacture ordered antidot arrays of magnetic oxides with variable lattice parameters.
Keywords: antidot arrays; atomic layer deposition; focused ion beam; magnetic properties; thermal reduction